Pasternak-Studien II Die Dimension des Weiblichen im Schaffen Boris Leonidovic Pasternaks. Inspirationsquellen, Erscheinungsformen und Sinnkonzeptionen - Uhlig, Andrea (Marburger Abhandlungen zur Geschichte und Kultur Osteuropas, 2001)
The series Marburg Treatises on the History and Culture of Eastern Europe contains monographs and anthologies from the field of Slavic Studies. Besides literary and historical studies, which are the thematic focus of the series, studies in linguistics are also considered.